Factors affecting the acculturation strategies of unaccompanied refugee minors in Germany - Garbade, Maike; Eglinsky, Jenny; Kindler, Heinz; Rosner, Rita; Sachser, Cedric; Pfeiffer, Elisa (Frontiers in Psychology, 2023)
Background: Different acculturation strategies might be related to different mental health outcomes and social participation of unaccompanied refugee minors (URMs), but little is known about which factors influence this acculturation process. Therefore, the aim of this investigation was to examine the impact of individual, stress-related, and contextual factors on the acculturation process of URMs in Germany. Methods: A sample of N = 132 URMs living in child and youth welfare service facilities in Germany completed questionnaires about their acculturation orientation, traumatic experiences, daily stressors, asylum stress, and perceived social support between June 2020 and October 2021. This investigation is part of the multi-center randomized control trial BETTER CARE. Data were analyzed descriptively and via multiple hierarchical regression. Results: Integration (43.5%) and Assimilation (37.1%) were the most common acculturation strategies used by URMs. Multiple hierarchical regression models showed that daily stressors (e.g. the lack of money) were associated with a stronger orientation towards the home country, whereas traumatic events were associated with a weaker orientation towards their home country. No significant predictors were found for the orientation towards the host country. Discussion: Overall, URMs in Germany showed favorable acculturation strategies. Nevertheless, daily stressors and traumatic experiences might influence this process. The implications for practitioners and policymakers are discussed with a view to further improving the acculturation process of URMs in Germany.